Extreme ultraviolet astronomy - Barstow, Martin A. (Martin Adrian), 1958- (Cambridge astrophysics series, 2003)
Describes the development of astronomy in the Extreme Ultraviolet wavelength range, from the first rocket-based experiments to the latest satellite missions. This timely book for graduate students and researchers comes at the end of a major phase of discovery in the field.